Penguatan Kelembagaan Petani dalam Mendukung Pengembangan Kelapa Sawit di Kawasan Transmigrasi Harus Muda Jaya - Ima Dwitawati; Fathya Miyagi; Andhini Shafa Isnain; Khaira Khirnica; Rahmad Syah Putra; Setiyo Gunawan (Sewagati, 2026)
This community engagement program aimed to develop a comprehensive understanding of the development design for a priority commodity within a transmigration area located in Harus Muda Jaya, Bireuen Regency, Aceh. The program was implemented through a multi-stakeholder collaboration involving central and local government agencies, academics, religious leaders, professional associations, business actors, and local communities. The findings indicate that the Harus Muda Jaya Transmigration Area has been designated as a priority locus for oil palm development due to its high land suitability, proximity to regional markets and palm oil mills (POMs), and the active participation of transmigrant communities. Oil palm has become the primary source of household income in the Transmigration Settlement Units (UPT) of Cot Kruet, Lhok Tanoh (Krueng Meuseugob), and Bukit Cerana, supported by favorable biophysical conditions, including stable rainfall patterns, flat topography, and suitable soil characteristics. Despite these advantages, the area continues to face several structural challenges, including the sale of Fresh Fruit Bunches (FFB) in unprocessed form, heavy dependence on intermediaries, limited irrigation facilities and farm-to-market road infrastructure, as well as increasing exposure to climate-related risks. Accordingly, the proposed development pathway emphasizes institutional strengthening at the farmer level through capacity building of farmer groups, cooperatives, and village-owned enterprises (BUMG). Such institutional reinforcement is considered a critical prerequisite for enabling farmers to engage in more balanced partnerships with palm oil mills, access direct marketing channels, and establish more transparent and efficient FFB trading arrangements.